TINJAUAN PERSEPSI MAHASISWA TENTANG PEMAHAMAN KODE ETIK PROFESI AKUNTAN - Fabio Bolanda Sandy; Muhammad Afif Setyawan; Tiara Rani Santoso; Hesiya May Ghaisani; Hesti Fajarsari (AKUNTANSI DEWANTARA, 2025)
The purpose of this study is to evaluate accounting students' perceptions of the understanding of the ethics of the accounting profession in several universities in Central Java. The ethics of the accounting profession plays a significant role in shaping professional behavior. These decisions will ultimately influence the level of public trust in the credibility of financial reports. The researcher used a quantitative approach with a questionnaire (Google Form) as the research instrument. From several universities in Central Java, the researcher obtained 64 student samples. In sampling, the researcher used a purposive sampling method with the criteria of students who have taken courses in Audit and Business Ethics. Later, the data will be analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, T-tests, and F-tests. The results of the study indicate that Gender, Ethical Knowledge and Love of Money have a positive effect on students' understanding of the code of ethics of the accounting profession. In addition, the Education Level variable does not affect students' perceptions of the understanding of the code of ethics of the accounting profession. This study is expected to improve students' understanding of the importance of ethical attitudes in the accounting profession.